King go beyond the dream to discover the man - Beacham, Tim.; Keenan, Tom.; Guy, Shoshana; Brokaw, Tom.; NBC News.; History Channel (Television network); Arts and Entertainment Network; New Video Group ([New York, NY] : A & E Television Networks : Distributed by New Video, 2008)
Forty years after Martin Luther King's assassination, newsman Tom Brokaw, takes viewers through the extraordinary life and times of America's civil rights visionary. Go beyond the legend to portray the man, the questions, the myths, and the relevance of Dr. King's message in today's world.
DVD; Dolby Digital stereo., subatomic digital.
Closed-captioned.
Narrator, Tom Brokaw ; interviews with: Martin Luther King III, Andy Young, Harry Belafonte, Bill Clinton, Condoleezza Rice, Bono, Forest Whitaker, Chuck D.
Originally broadcast by The History Channel in 2008.
Special features: "Voices of civil rights" full-length documentary.
Executive producers Knute Walker.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968.; African American civil rights workers -- United States -- Biography; Assassination -- United States; United States -- History -- 1961-1969.; Documentary -- Television special; Biographical (Nonfiction) -- Television special; King, Martin Luther, -- Jr., -- 1929-1968.; African American civil rights workers -- United States -- Biography; Assassination -- United States; United States -- History -- 1961-1969.; Documentary television programs; Biographical television programs; Video recordings for the hearing impaired; Nonfiction television programs; Television programs; Documentary -- Television special; Biographical (Nonfiction) -- Television special